1975
DOI: 10.3109/00016347509156743
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen‐Fibrin Degradation Products in Menstrual Blood from Women with Normal and Excessive Menstrual Blood Losses

Abstract: Fibrinogen-fibrin degradation products, FDP, in menstrual blood during the first three days of menstrual blood during the first three days of menstruation have been investigated. Two groups of women were studied, those with normal menstrual blood loss (15 women, mean loss 30 ml, range 8-60 ml) and those with menorrhagia (14 women, mean loss 222 ml, range 107-729 ml). The following results were obtained: 1). The FDP concentrations decreased during menstruation in both groups. 2). The FDP concentrations in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…However, work is being pursued concerning endometrial and myometrial tissue production in vitro of these two prostaglandins (Rees et al 1984). In addition, factors other than prostaglandins have to be considered since abnormalities in fibrinolytic activity have also been described in menorrhagia (Rybo 1966;Hahn & Rybo 1975) and heparin-like activity has been found in uterine fluid (Foley et al 1978). Therefore much basic research remains to be undertaken if we are to understand the mechanisms involved in the pathogenesis of menorrhagia and dysmenorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…However, work is being pursued concerning endometrial and myometrial tissue production in vitro of these two prostaglandins (Rees et al 1984). In addition, factors other than prostaglandins have to be considered since abnormalities in fibrinolytic activity have also been described in menorrhagia (Rybo 1966;Hahn & Rybo 1975) and heparin-like activity has been found in uterine fluid (Foley et al 1978). Therefore much basic research remains to be undertaken if we are to understand the mechanisms involved in the pathogenesis of menorrhagia and dysmenorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from this department (Haynes et al, 1979) have suggested that most women with regular but excessive menstrual blood loss (>80 ml per period) are ovulating and that serum levels throughout the menstrual cycle of gonadotrophins, oestradiol, and progesterone in women with menorrhagia are no different from those in women with normal menstrual blood loss. In the absence of any obvious abnormality of pituitary-ovarian function, the cause of this unexplained heavy menstruation could be due to an abnormality in function of the endometrium or myometrium or in their blood supply, and a defect in prostaglandin synthesis and/or metabolism (Downie et al, 1974;Smith, 1979) or in fibrinolytic activity (Rybo, 1966;Hahn and Rybo, 1975) could be postulated.…”
Section: Discussionmentioning
confidence: 99%
“…That normal menstrual blood appears to be fibrinolytically exhausted strongly suggests that other factors within the endometrium are responsible for the heavy menstrual blood loss that is ameanable to treatment with synthetic antifibrinolytic agents.4 20 The excellent technical assistance of Mrs F Daniels is acknowledged. This study was supported by grants from the British Heart Foundation (grant no 83/10), the Medical Research Council, and Parke-Davis Pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%